Perancangan Sistem Informasi Konsultasi Dokter Klinik Rahma Bukittinggi - Ridho, Muhammad (Journal of Information System and Technology (JOINT), 2025)
The design of this Information System has had a good impact on the Rahma Bukittinggi clinic, where initially the system for recording patients manually by doctors still used paper and books in recording patient status at the Rahma Clinic Bukittinggi with this research regarding the Design of the Rahma Doctor Consultation Information System in Bukittinggi, so that recording patient status is faster compared to using paper manually. The method used in designing the Doctor Consultation Information System at the Rahma Clinic in Bukittinggi is RAD. There are three stages in planning the information system design, namely the planning stage, the design workshop stage and the implementation stage. This method uses the UML development system as the basis. The tools in designing this Information System have had a good impact at the Rahma Clinic, Bukittinggi, helping the Rahma Clinic to be computerized in recording patient status so that services are faster and more accurate.